Correlation of filament distortion and RRR degradation in drawn and rolled PIT and RRP Nb3Sn wires. (11th July 2016) - Brown, M; Tarantini, C; Starch, W; Oates, W; Lee, P J; Larbalestier, D C
Abstract: PIT and RRP ® Nb3 Sn strands are being developed for high field accelerator magnet upgrades for the high luminosity LHC. Here we report a quantitative study of the shape and position of PIT filaments and RRP ® sub-elements after rolling lengths of unreacted PIT and RRP ® round wires to simulate cabling deformation. In the as-drawn condition, filament shape distortion occurs preferentially in the outer ring filaments. By contrast, rolling induces non-uniform shear bands that generate greater distortion of inner ring filaments. By making a full digitization of the shapes of all filaments, we find that a critical distortion occurs for thickness reductions between 10% and 20% when filament shapes in inner filament rings heavily degrade, especially in the vicinity of the strong 45 ° shear bands imposed by the rolling. It is well known that maintaining diffusion barrier integrity is vital to retaining adequate RRR in the stabilizing copper needed for magnet stability. Diffusion barrier breaks occur preferentially in these distorted inner filaments and drive local Sn leakage during reaction, increasing RRR degradation.